2010
DOI: 10.1097/mpg.0b013e3181a70af4
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Eosinophilic Esophagitis: A True Association

Abstract: The prevalence of EE in this cohort of children with CD is at least 4%. This is likely to be an underestimation because only 121 of 250 children had concurrent esophageal biopsies. Coexistent EE should be kept in mind in children undergoing endoscopy for suspected CD, and esophageal biopsies should be obtained, irrespective of whether esophageal mucosa appears normal or abnormal at endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
5
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 20 publications
3
78
5
3
Order By: Relevance
“…Ooi et al (1) reported the prevalence of EE to be 3.2% among 221 children with CD. Leslie et al (2) reported the prevalence of EE to be 4% among 250 children with CD and in this study 3 of 10 children were reported to have symptoms of CD and EE, esophagus appeared normal at endoscopy, but biopsies showed evidence of EE similar to our case. Another study showed that approximately 30% of children diagnosed as having EE had normal-appearing esophageal mucosa at endoscopy (6).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Ooi et al (1) reported the prevalence of EE to be 3.2% among 221 children with CD. Leslie et al (2) reported the prevalence of EE to be 4% among 250 children with CD and in this study 3 of 10 children were reported to have symptoms of CD and EE, esophagus appeared normal at endoscopy, but biopsies showed evidence of EE similar to our case. Another study showed that approximately 30% of children diagnosed as having EE had normal-appearing esophageal mucosa at endoscopy (6).…”
Section: Discussionsupporting
confidence: 59%
“…Our patient presented with only abdominal pain and constipation. Leslie et al (2) reported that 1 of 10 children with CD and EE presented with only abdominal pain and normal-appearing esophageal mucosa at endoscopy but biopsies showed evidence of EE, as in our case. However, other diseas that are associated with esophageal eosinophilia were also excluded for our patient with clinical and laboratory findings.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…It is important, however, to understand that primary EoE may co-exist with at least some of these disorders. For example, treatment of celiac disease with a gluten-free diet will result in concomitant resolution of EoE in \50 % of cases [4]. Symptoms in EoE are broad, often overlap with other diseases, and can vary based on age.…”
Section: Introductionmentioning
confidence: 99%